Global Impact of Renewable Energy Innovations: Dampak Global dari Inovasi Energi Terbarukan - Shalsa Ervina Dia Sari; Hasan Ubaidillah (Academia Open, 2024)
This study explores how product quality, price, and promotional attractiveness impact consumer purchasing decisions on Shopee in Sidoarjo, Indonesia, using a quantitative descriptive approach with 96 respondents. The findings indicate that higher product quality and attractive promotions positively influence purchase intent, while price sensitivity also plays a role. These insights are valuable for businesses in online marketplaces like Shopee, emphasizing the importance of maintaining high product quality, competitive pricing, and effective promotions to enhance consumer decisions and market performance. Highlight: Online consumer behavior analysis Quality and price influence purchases Promotions impact buying decisions Keyword: consumer behavior, online marketplace, purchase decisions, product quality, promotional attractiveness